2020
DOI: 10.1101/2020.07.13.199703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A highly expressing, soluble, and stable plant-made IgG fusion vaccine strategy enhances antigen immunogenicity in mice without adjuvant

Abstract: SummaryWhile therapeutics based on fusing a protein of interest to the IgG Fc domain have been enormously successful, fewer studies have investigated the vaccine potential of IgG fusions. In this study, we systematically compared the key properties of a panel of plant-made IgG fusion vaccine candidates targeting Zika virus envelope domain III (ZE3). Complement protein C1q binding of the IgG fusions was enhanced by: 1) ZE3 fusion to the IgG N-terminus; 2) removal of the IgG light chain or Fab regions; 3) additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…As the coronavirus disease 2019 (COVID 19) is pandemic across the world, over 103 million cases of COVID 19 have been reported and more than 2 million people have been claimed. It is urgent to develop the vaccine of COVID 19 to help human get rid of the threat of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the coronavirus disease 2019 (COVID 19) is pandemic across the world, over 103 million cases of COVID 19 have been reported and more than 2 million people have been claimed. It is urgent to develop the vaccine of COVID 19 to help human get rid of the threat of it.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that IgG-based scaffold can enhance the solubility and stability of fusion protein, generating robust and long-lasting immune responses [18][19][20]. The fragment crystallizable (Fc) region is required for killing of virus-infected cells by complement-dependent cytotoxicity (CDC) and by antibodydependent cellular cytotoxicity (ADCC) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that IgG-based scaffold can enhance the solubility and stability of fusion protein, generating robust and long-lasting immune responses (18)(19)(20). The fragment crystallizable (Fc) region is required for killing of virus-infected cells by complement-dependent cytotoxicity (CDC) and by antibody-dependent cellular cytotoxicity (ADCC) (21,22).…”
Section: Introductionmentioning
confidence: 99%